Laparoscopic common bile duct exploration. Issue 11 (14th August 2014) - Chan, D S Y; Jain, P A; Khalifa, A; Hughes, R; Baker, A L
Abstract: Background: Laparoscopic common bile duct exploration (LCBDE) is a safe and effective single-stage treatment for choledocholithiasis in the elective setting. The outcomes after LCBDE in the emergency setting are unknown. The aim of this study was to compare the outcomes following elective and emergency LCBDE for choledocholithiasis. Methods: Details of all patients who underwent LCBDE for choledocholithiasis between August 2003 and August 2013 were analysed retrospectively. The primary outcome measure was common bile duct (CBD) stone clearance rate. Secondary outcome measures were conversion rate, morbidity, mortality and length of hospital stay. Results: Some 215 consecutive patients (57 male; median age 65 (range 14–92) years) underwent LCBDE. Some 121 procedures were performed electively and 94 as an emergency. Forty-five patients (48 per cent) presented with obstructive jaundice or cholangitis in the emergency LCBDE group compared with 15 (12·4 per cent) in the elective group ( P < 0·001). The CBD stone clearance rate was similarly high in both groups (96 versus 96·7 per cent respectively; P = 0·557). There were no significant differences in conversion rate (6 versus 4·1 per cent), morbidity (5 versus 6·6 per cent), mortality (2 versus 0 per cent) or median length of stay (3 days) between groups. Two patients died, both following emergency LCBDE. Conclusion: LCBDE can be performed safely and effectively in both elective and emergency settings. Abstract : Good as elective or emergency procedure